Non‐Newtonian Fluid State K–Na Alloy for a Stretchable Energy Storage Device. Issue 10 (15th August 2019) - Zhang, Liyuan; Li, Yuqian; Zhang, Shengzhao; Wang, Xiuli; Xia, Xinhui; Xie, Dong; Gu, Changdong; Tu, Jiangping
Abstract: Potassium–sodium alloy (KNA) is defined as an attractive candidate for energy storage devices in space probes. Nevertheless, high surface tension and fluidity of KNA make the electrode difficult to shape which results in unstable electrochemical properties. In this contribution, a low surface tension and paintable non‐Newtonian fluid state KNA and Super P composite (KNA@C) fabricated by a simple stirring strategy is reported. The formation of hydroxides in the KNA@C composite gives rise to stable liquid alloy–electrolyte and liquid alloy–current collector interfaces. Moreover, the KNA@C coating can be well adhered on the surface of the current collector, and keeps stable under bending, folding, and stretching. In addition, an energy conversion device with stretchable and flexible properties is assembled based on the KNA@C anode. Excitingly, the blub keeps shining even extending the device to more than 200% and twisting it to ±90° repeatedly. This research provides an optimistic prospect to achieve stretchable and flexible dendrite‐free alkali metal batteries. Abstract : Paintable semisolid K‐Na alloy@Super P is prepared by a facile room‐temperature stirring process. Due to good structure stability and good adhesion, the designed semisolid Na–K Alloy@Super P electrode exhibits noticeable electrochemical performance. In addition, an energy conversion device with stretchable and flexible properties is assembled based on the Na–K alloy@Super P anode.